Equality of Opportunities, Redistribution and Fiscal Policies : The Case of Liberia - Abras, Ana; Cuesta, Jose (2012)
This paper brings back the fiscal angle to the analysis of equal opportunities both by connecting traditional benefit-incidence analysis of public spending with equal opportunities and by conducting ex-ante micro-simulations on the fiscal cost of equal opportunity policies in education. Four simulations are conducted in Liberia, a country devastated by a civil war, with serious educational enrollment gaps and fiscal policies highly dependent on international aid. Results for the simulated policy scenarios (increases in teachers' salaries, elimination of both fee and non-fee costs borne by households, and targeting public spending on education to rural schools) point to very modest redistributive effects but very different patterns of winners and losers among groups of children in Liberia.